The Effect of Learning Resources, School Environment, and School Culture in Increasing Accounting Student Learning Outcomes - Oktavianingrum, Fauziyah; Asmawan, Moh. Chairil (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to analyze the influence of learning resources, school environment, and school culture on student learning outcomes in the Accounting Department at SMK Negeri 6 Surakarta. A quantitative approach was employed using an explanatory survey method. The sample consisted of 179 students selected through proportionate stratified random sampling from a total population of 323 students. Data were collected using a four-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression. The results showed that the three independent variables simultaneously had a significant effect on student learning outcomes (Prob. F = 0.000; R² = 0.719). Partially, school culture had the most dominant influence (β3= 0.440; p = 0.000), followed by the school environment (β2= 0.270; p = 0.000), and learning resources (β1= 0.134; p = 0.024). These findings underscore the importance of a holistic approach in efforts to improve the quality of vocational education, particularly through the optimization of learning resource management, the creation of a conducive school environment, and the strengthening of school culture. This study contributes to the development of an integrated conceptual model relevant to managerial practices and educational policy at the vocational high school level.